Análise econômica e de risco de sistemas de produção de leite no Sul de Minas Gerais - Souza, Pablo José Freitas De (2021)
Dairy activity is important for Brazil, due to Brazil being the fourth largest world producer of milk. For this reason, milk production generates jobs and income, in addition to feeding families, mainly for the so-called family agriculture that produces most of the milk in the country. However, the small producer is the production chain weakest part and the current changes are increasingly demanding a lower cost and higher quality milk production. In fact, the cost, economic viability and production systems risks analysis are needed for producer’s decision making regarding these investments. Thus, the proposal in question has the general objective of conducting a study of economic viability and a risk analysis of milk production systems for pasture and compost barn in the southern region of the state of Minas Gerais. Hence, the study was done in two stages. First, the costing structures of four properties were developed, two from each system, identifying its main components and using the EVA (economic value added), NPV (net present value) and IRR (internal rate of return) indicators to study the economic viability. Sensitivity analyzes were also carried out considering the price of feed and milk. The properties are located in the municipalities Carvalhópolis, Piranguinho, Boa Esperança and Carmo do Rio Claro. In the second stage, 4 scenarios were built, two from each production system, with different productivity and an economic feasibility study and risk analysis using the Monte Carlo simulation was made. It was found that the pasture-based production system properties managed to obtain lower total costs and, in most cases, better results in the economic analysis. Particularly, a property in Cavalhópolis was found to be unfeasible. However, except for the property of Carmo do Rio Claro, the properties were very sensitive to small price variations in the variables studied. A Monte Carlo simulation was carried out and a changeover from the pasture-based system to the compost barn only proved viable above a thousand liters of production daily, furthermore the pasture production system could lead to higher returns for the owner.